Solar energy for greenhouse drying: Performance evaluation of parabolic trough solar collector with two-axis tracking system - Das, Mehmet; Pektezel, Oguzhan; Simsek, Mithat (Pergamon-Elsevier Science Ltd, 2025)
This study was conducted to develop a solution for the efficient and sustainable use of solar energy in food drying in response to the depletion of fossil fuels, environmental concerns, and increasing energy demand. The motivation is to improve energy efficiency and provide environmentally friendly alternatives in food drying applications. This study experimentally evaluated the performance of a greenhouse dryer equipped with a parabolic trough solar collector (PTSC) with an air-fluidized, dual-axis solar tracking system (STS). The experiments were conducted between June 12 and June 17, 2023, in Tokat, Turkey, located between 39 degrees 51 '-40 degrees 55 ' North latitudes and 35 degrees 27 '-37 degrees 39 ' East longitudes, between 10:00 a.m. and 5:00p.m. each day. In the apple drying experiments, solar radiation was continuously directed to the collector at an optimum angle with STS, and energy efficiency and exergy efficiency increased by 28.7 % and 36.2 %, respectively. Drying time decreased by 57.2 %, and the product surface temperature reached 76.1 degrees C. With the effect of STS, solar radiation on the system increased by an average of 18.8 %, and drying efficiency improved by 47.2 %. The study's originality is using air-fluid in the tube system, which is equipped with a dual-axis, fully automatic solar tracking mechanism. In the literature, water-based and single-axis systems have generally been studied. This study introduces an innovation that enhances the efficiency and sustainability of solar energy usage in food drying. It offers a transformative approach to integrating energy systems within agricultural practices, paving the way for a more effective and environmentally friendly future in food drying.
Keywords: Parabolic trough solar collector; Greenhouse dryer; Heat and mass transfer; Two-axis solar tracking system